Initiation of Increasing Tuberculosis Medication Supervisors Roles: An Action Research Approach - Arini, Merita; Puspitosari, Warih Andan; Ferawati, Bangkit Ina (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Indonesia is ranked second in the number of Tuberculosis (TB) cases worldwide. TB patients and their families experience a complex burden. Hence, support and strengthening TB medication supervisors (Pengawas Minum Obat/ PMO) role is needed.  The aim of this study was to enhance the Community Health Center (CHC)-based PMOs’ role by improving their knowledge and strengthening peer group support. The method used was an action research cycle with four stages. The diagnosis stage was carried out by consensus decision making group with CHC to determine priority problems, namely the need to increase basic knowledge of TB and its treatment. Optimizing peer group was also necessary, as the Self Reporting Questionnaire-20 showed that more PMOs from patient families have psychological problems than cadres.  The planning stage was conducted by preparing educational sessions and creating educational media. The action stage was a quasi-experimental (without control, non-randomization)—an educational talk show provided by the TB program manager, pulmonologist, and psychiatrist. Peer groups are also activated by triggering shared media education and discussion. At the evaluation stage, knowledge was measured by giving pre and post-tests (n= 21, total sampling). The results of the analysis using the Wilcoxon's Signed Ranks Test showed that participants' knowledge had increased significantly (p=0.000; r=0.59). In conclusion, education can increase PMO knowledge as an initial step to strengthen their role in supporting the success of TB treatment. Innovation, cross-sector assistance, and support are needed to enable the PMO to succeed in the TB program.